Mechanisms of action and outcomes for students in Recovery Colleges - Toney, Rebecca; Elton, Daniel; Munday, Emma; Hamill, Kate; Crowther, Adam; Meddings, Sara; Taylor, Anna; Henderson, Claire; Jennings, Helen; Waring, Justin; Pollock, Kristian; Bates, Peter; et al. (American Psychiatric Publishing, 2018)
Objective Recovery Colleges are widespread, with little empirical research on how they work and outcomes they produce. This study aimed to co-produce a change model characterising mechanisms of action and outcomes for mental health service users attending as students at a Recovery College. Methods A systematised review identified all Recovery College publications. Inductive collaborative data analysis by academic researchers and co-researchers with lived experience of ten key papers informed a theoretical framework for mechanisms and outcome for students, which was refined through deductive analysis of 34 further publications. A change model was co-produced and then refined through stakeholder interviews (n=33). Results Three mechanisms of action for Recovery College students were identified: empowering environment (safety, respect, supporting choices), enabling different relationships (power, peers, working together) and facilitating personal growth (e.g. co-produced learning, strengths, celebrating success). Outcomes were change in the student (e.g. self-understanding, self-confidence) and changes in the student’s life (e.g. occupational, social, service use). A co-produced change model mapping mechanisms of action to outcomes was created. Conclusions The key features identified as differentiating Recovery Colleges from traditional services are an empowering environment, enabling relationships and growth orientation. Recovery Colleges may benefit most attenders, but mental health service users to particularly encourage to enrol may include those who lack confidence, those who services struggle to engage with, those who will benefit from exposure to peer role models, and those lacking social capital. The change model provides the first testable characterisation of mechanisms and outcomes, allowing formal evaluation of Recovery Colleges.